Targeting E2F1–DNA complexes with microgonotropen DNA binding agents - Chiang, Shu-Yuan (The National Academy of Sciences of the USA, 1997)
Microgonotropen (MGT) DNA binding drugs, which consist of an A+T-selective DNA minor groove binding tripyrrole peptide and polyamine chains attached to a central pyrrole that extend drug contact into the DNA major groove, were found to be extraordinarily effective inhibitors of E2 factor 1 (E2F1) association with its DNA promoter element (5′-TTTCGCGCCAAA). The most active of these drugs, MGT-6a, was three orders of magnitude more effective than distamycin and inhibited complexes between E2F1 and the dihydrofolate reductase promoter by 50% at 0.00085 μM. A relationship was found between the measured equilibrium constants for binding of MGTs to the A+T region of d(GGCGA(3)T(3)GGC)/d(CCGCT(3)A(3)CCG) and their inhibition of complex formation between E2F1 and the DNA promoter element. A representative of the potent MGT inhibitors was significantly more active on inhibition of E2F1–DNA complex formation compared with disruption of a preexisting complex.